2021
DOI: 10.1093/genetics/iyab074
|View full text |Cite
|
Sign up to set email alerts
|

Rapid detection of inter-clade recombination in SARS-CoV-2 with Bolotie

Abstract: The ability to detect recombination in pathogen genomes is crucial to the accuracy of phylogenetic analysis and consequently to forecasting the spread of infectious diseases and to developing therapeutics and public health policies. However, in case of the SARS-CoV-2, the low divergence of near-identical genomes sequenced over a short period of time makes conventional analysis infeasible. Using a novel method, we identified 225 anomalous SARS-CoV-2 genomes of likely recombinant origins out of the first 87,695 … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
60
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 65 publications
(66 citation statements)
references
References 26 publications
1
60
0
Order By: Relevance
“…Our extensively optimized implementation of RIPPLES allows it to search the entire phylogenetic tree and detect recombination both within and between SARS-CoV-2 lineages without a priori defining a set of lineages or clade-defining mutations. This is a key advantage of our approach relative to other methods that cope with the scale of SARS-CoV-2 datasets by reducing the search space for possible recombination events (e.g., (9,10,14)). RIPPLES discovers 239 recombination events within branches of the same Pango lineages.…”
Section: Fig 2 Ripples Detects An Excess Of Recombination In the Spike Protein Region (A)mentioning
confidence: 99%
“…Our extensively optimized implementation of RIPPLES allows it to search the entire phylogenetic tree and detect recombination both within and between SARS-CoV-2 lineages without a priori defining a set of lineages or clade-defining mutations. This is a key advantage of our approach relative to other methods that cope with the scale of SARS-CoV-2 datasets by reducing the search space for possible recombination events (e.g., (9,10,14)). RIPPLES discovers 239 recombination events within branches of the same Pango lineages.…”
Section: Fig 2 Ripples Detects An Excess Of Recombination In the Spike Protein Region (A)mentioning
confidence: 99%
“…A number of more recent reports have utilized methods based on classifying sequences into clades, and searching for those that appear to carry a mix of mutations characteristic to more than one clade. VanInsberghe et al (2021) identified 1,175 possible recombinants out of 537,000 analyzed sequences; Varabyou et al (2021) identified 225 possible recombinants out of 88,000; Jackson et al (2021) have identified a small number of putative recombinants circulating in the United Kingdom. These methods are sensitive to the classification of sequences into clades, do not allow for the detection of intra-clade recombinants (thus underestimating the overall extent of recombination), and do not incorporate a framework for quantifying how likely it is that an observed pattern of incompatibilities has arisen through recombination rather than recurrent mutation.…”
Section: Introductionmentioning
confidence: 99%
“…Genome replication infidelity [ 98 ], intra-host viral evolution in prolonged infections, which predominantly occurs in immunocompromised individuals [ 54 , 99 – 102 ], host RNA-editing systems [ 103 ], and within-host recombination events occurring subsequently to co- or super-infection with different circulating strains [ 104 ] are considered the potential sources of SARS-CoV-2 genome sequence variability. Random mutations account for the majority of genomic variations [ 103 , 105 ]. Although most immunocompromised persons effectively clear SARS-CoV-2 infection, accelerated viral evolution in persistently infected immunocompromised individuals has been reported [ 54 , 103 , 106 ].…”
Section: Potential Sources Of Changes In the Sars-cov-2 Genomementioning
confidence: 99%
“…To the best of our knowledge, the first report of recombination between SARS-CoV-2 strains was published in August of 2020 [ 104 ]. In a few subsequent studies, recombination events between SARS-CoV-2 strains were surmised on the basis of defining markers of major clades or sequence variations in locally circulating strains [ 26 , 105 , 115 – 117 ]. It is not unlikely that some recombinant genomes have not been recognized because of technical issues in sequence analysis [ 105 ].…”
Section: Potential Sources Of Changes In the Sars-cov-2 Genomementioning
confidence: 99%
See 1 more Smart Citation